An Emerging Market's Reaction to Initial Modified Audit Opinions: Evidence from the Shanghai Stock Exchange* - CHEN, CHARLES J. P.; Su, Xijia; Zhao, Ronald (Contemporary Accounting Research, 2000)
This study investigates the valuation effect of modified audit opinions (MAOs) on the emerging Chinese stock market. Here, the term MAO refers to both qualified opinions and unqualified opinions with explanatory notes. The latter can be considered an alternative form of a qualified opinion in China. The institutional setting in China enables us to find compelling evidence in support of the monitoring role of independent auditing as an institution. First, we find a significantly negative association between MAOs and cumulative abnormal returns after controlling for effects of other concurrent announcements. Further, results from a by-year analysis suggest that investors did not reach negative consensus about MAOs' valuation effect until the second year, exhibiting the learning process of a market without prior exposure to MAOs. Second, we do not observe significant differences between market reaction to non-GAAP- and GAAP-violation-related MAOs. Third, no significant difference is found between market reaction to qualified opinions and market reaction to unqualified opinions with explanatory notes.